Myocardial Revascularization in COVID-19 Era - Sasmojo Widito (Heart Science Journal, 2021)
Coronavirus disease 2019 (COVID-19) is a highly contagious disease caused by the coronavirus 2 that causes severe acute respiratory syndrome (SARS-CoV-2). More discussion is required to achieve the balance between clinical benefit and risk in the treatment of acute coronary syndrome (ACS) patients with COVID-19. The current COVID-19 pandemic prompts the need to evaluate criteria for indication and efficacy of the general safety protocols and particular cardiac catheterization laboratory (CCL) procedures to safeguard the patient and healthcare professionals